2016
DOI: 10.1016/j.forsciint.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of drying blood pools

Abstract: Often blood pools are found on crime scenes which may provide information concerning the events that took place on the scene. However, there is a lack of knowledge concerning the drying dynamics of blood pools. This study focuses on the drying process of blood pools to determine what relevant information can be obtained for the forensic application. We recorded the drying process of blood pools with a camera while measuring the mass. We found that the drying process can be separated into five different stages:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
(30 reference statements)
0
38
0
Order By: Relevance
“…Blood dries relatively quickly depending on the temperature, humidity and presence/absence of wind [79][80][81]. A study by van Oorschot et al [82] showed that blood (15 and 30 µl) on a hard non-porous substrate will dry within 30-60 min (quicker in warmer temperatures), and that the transfer rates of blood, 5 min after deposition, declines exponentially until the deposit is dry.…”
Section: Source and Freshness /Moisture Contentmentioning
confidence: 99%
“…Blood dries relatively quickly depending on the temperature, humidity and presence/absence of wind [79][80][81]. A study by van Oorschot et al [82] showed that blood (15 and 30 µl) on a hard non-porous substrate will dry within 30-60 min (quicker in warmer temperatures), and that the transfer rates of blood, 5 min after deposition, declines exponentially until the deposit is dry.…”
Section: Source and Freshness /Moisture Contentmentioning
confidence: 99%
“…As stated by Laan et al [69], it's possible to distinguish five different drying stages, each with their own characteristics. The mass of a blood pool diminishes in a very reproducible manner, first linearly in time and then approaches a constant value.…”
Section: Pool Of Bloodmentioning
confidence: 99%
“…Certainly, evaporation and coagulation can significantly affect slower aspects of BPA such as the drying of pools of blood (8), the evaporation of sessile drops with microliter or larger volume, the formation of drip trails, and wicking in fabrics. These situations can exhibit time scales on the order of minutes as well as enhanced evaporation at contact line and can thus be influenced by evaporation or coagulation.…”
Section: Editormentioning
confidence: 99%